SOURCES OF PEDAGOGICAL SCIENCE OF BIOGRAPHY - Розман, Ирина (SWorldJournal, 2020)
: The article considers the study of sources of pedagogical biographies. Emphasis is placed on the ways and forms of personal research. Special attention is focused on the study of personal funds, diaries, archives, autobiographical micro-stories